Gene Body Methylation Confers Transcription Robustness in Mangroves During Long-Term Stress Adaptation - Wang, Yushuai; Dai, Aimei; Chen, Yiping; Tang, Tian (Frontiers in Plant Science, 2021)
Whether induced epigenetic changes contribute to long-term adaptation remains controversial. Recent studies indicate that environmentally cued changes in gene body methylation (gbM) can facilitate acclimatization. However, such changes are often associated with genetic variation and their contribution to long-term stress adaptation remains unclear. Using whole-genome bisulfite sequencing, we examined evolutionary gains and losses of gbM in mangroves that adapted to extreme intertidal environments. We treated mangrove seedlings with salt stress, and investigated expression changes in relation with stress-induced or evolutionarily-acquired gbM changes. Evolution and function of gbM was compared with that of genetic variation. Mangroves gained much more gbM than their terrestrial relatives, mainly through convergent evolution. Genes that convergently gained gbM during evolution are more likely to become methylated in response to salt stress in species where they are normally not marked. Stress-induced and evolutionarily convergent gains of gbM both correlate with reduction in expression variation, conferring genome-wide expression robustness under salt stress. Moreover, convergent gbM evolution is uncoupled with convergent sequence evolution. Our findings suggest that transgenerational inheritance of acquired gbM helps environmental canalization of gene expression, facilitating long-term stress adaptation of mangroves in the face of a severe reduction in genetic diversity.